WORK COMMITMENT AND TRANSFER OF TRAINING: A MEDIATED AND MODERATED MODEL THROUGH SEM-PLS EVIDENCE FROM PAKISTAN - Kori, Niaz Hossain; Abdul Ghani Azmi , Ilhaamie (Online Journal of Islamic Management and Finance (OJIMF), 2022)
This study aims to assess the relationship between independent variable work commitment (WC) and dependent variable transfer of training (TOT) with mediated variable motivation to transfer and moderated variable Islamic personality characteristics. This mechanism is a multivariate quantitative study, therefore, applied mediated moderated model through the PLS-SEM approach. The study targets to assess the relationships among latent constructs to give new insights into the HRM practices in organizations. The data are collected from the Shariah-compliant banks in Pakistan. The statistical reliability and validity were established and based on hypotheses. The findings are formed to confirm the measurement model first and then the structural model to investigate relationships among constructs. The results of the study reveal that there exists a significant and positive relationship between constructs of work commitment and transfer of training. The mediating variable motivation to transfer (MOT) plays its role partially between the independent variable (WC) and dependent variable (TOT). Moreover, the moderating variable Islamic personality characteristics (IP) interestingly make a stronger relationship between work commitment and transfer of training by its moderating effect which is positive and statistically significant. Hence, this study provides a clear picture for the practical and professional assessment of employees regarding the transfer of training to improve the organizational practices in human resource management practices for all types of organizations in general and shariah-compliant banking organizations in particular, thus, the study has professional and practical importance in this connection. This research with sustainable consideration has an original and novel contribution of authors to the literature.